Severe lipoid pneumonia following attempted suicide by mineral oil immersion. Issue 6 (June 1996) - Hussain, I R; Edenborough, F P; Wilson, R S; Stableforth, D E
Abstract : Following an attempted suicide by drowning in a vat of mineral oil, a previously fit man survived the usually fatal lipoid pneumonia resulting from total immersion after intensive support and prolonged steroid therapy with recovery of chest radiography and pulmonary function at one year.